Efektivitas Metode Imla’ terhadap Peningkatan Kemampuan Siswa dalam Menulis Bahasa Arab - Imam Asrofi; Abdul Halim (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2021)
Facts on the ground, there are still many students who find it difficult to write in Arabic according to the rules of writing style caused by differences in intellectual abilities, physical abilities, family backgrounds, habits and learning approaches that are sometimes very striking between one student and another student. Therefore, learning techniques are needed that can improve students' ability to write Arabic. IMLA is a learning technique to justify as well as improve writing that needs improvement. The purpose of this study is based on the aim of obtaining empirical data regarding the effectiveness of the application of the IMLA method in writing Arabic for class XI students of senior High School Cililin, Sumur Bandung, West Bandung. This research is an experimental research type. The population in this study was class XI senior High School Cililin, Sumur Bandung, West Bandung, amounting to 37 students. The research data was obtained by presenting a dictation skill test IMLA and proved by the results of the t-test. From the results of data analysis, it can be obtained t-count (10.87) > t-table (1.687) with a significant level of 5%. West in writing Arabic.